Erving Goffman and modern sociology - Manning, Philip (Key Contemporary Thinkers, 1992)
The work of Erving Goffman (1922-82) has had an enormous impact throughout the social sciences, yet his writings have not received detailed scrutiny. This book not only assesses all of Goffman's seminal works but also demonstrates why his thought has been so influential to modern sociology. The book both explores and complements Goffman's ideas, drawing on the structuration theory of Anthony Giddens and on ethnomethodology to situate Goffman's work in relation to other, more systematic social theories while keeping an eye on how Goffman's work questions their basic presuppositions.